1996
DOI: 10.1002/(sici)1096-9861(19960219)365:4<659::aid-cne11>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and columnar patterns of geniculocortical projections in the cat: Relationship to cytochrome oxidase

Abstract: We examined the laminar and columnar arrangement of projections from different layers of the lateral geniculate nucleus (LGN) to the visual cortex in the cat. In light of recent reports that cytochrome oxidase blobs (which in primates receive specific geniculate inputs) are also found in the visual cortex of cats, the relationship between cytochrome oxidase staining and geniculate inputs in this species was studied. Injections of wheat germ agglutinin-conjugated horseradish peroxidase were made into the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 25 publications
(29 reference statements)
7
44
3
Order By: Relevance
“…In the present study, we have confirmed the previous observations of Rosenquist (1980, 1983) that the Cparv conveys W-cell information and projects widely to both the striate and the extrastriate cortical areas and the observations of Boyd and Matsubara (1996) and others that projection terminals from the Cparv show a laminar pattern different from that of laminae A, which convey X-and Y-cell information in areas 17 and 18 (Fig. 10).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, we have confirmed the previous observations of Rosenquist (1980, 1983) that the Cparv conveys W-cell information and projects widely to both the striate and the extrastriate cortical areas and the observations of Boyd and Matsubara (1996) and others that projection terminals from the Cparv show a laminar pattern different from that of laminae A, which convey X-and Y-cell information in areas 17 and 18 (Fig. 10).…”
Section: Discussionsupporting
confidence: 92%
“…These results largely confirm previous findings from anterograde axon injection (LeVay and Gilbert, 1976;Ferster and LeVay 1978;Freund et al, 1985;Humphrey et al, 1985a,b;Boyd and Matsubara, 1996) and retrograde (Leventhal, 1979) studies. Boyd and Matsubara (1996) concluded that, although projections from laminae A occupy the full vertical extent of layer IV, the Cparv projects to layers I, III, and Va in area 17 without overlapping the projection layers from laminae A.…”
Section: Areas 17 and 18supporting
confidence: 92%
See 3 more Smart Citations